Post-transcriptional Modulation of Sphingosine-1-Phosphate Receptor 1 by miR-19a Affects Cardiovascular Development in Zebrafish - Guzzolino, Elena; Chiavacci, Elena; Ahuja, Neha; Mariani, Laura; Evangelista, Monica; Ippolito, Chiara; Rizzo, Milena; Garrity, Deborah; Cremisi, Federico; Pitto, Letizia (Frontiers in Cell and Developmental Biology, 2018)
Sphingosine-1-phosphate is a bioactive lipid and a signaling molecule integrated into many physiological systems such as differentiation, proliferation and migration. In mammals S1P acts through binding to a family of five trans-membrane, G-protein coupled receptors (S1PRs) whose complex role has not been completely elucidated. In this study we use zebrafish, in which seven s1prs have been identified, to investigate the role of s1pr1. In mammals S1PR1 is the most highly expressed S1P receptor in the developing heart and regulates vascular development, but in zebrafish the data concerning its role are contradictory. Here we show that overexpression of zebrafish s1pr1 affects both vascular and cardiac development. Moreover we demonstrate that s1pr1 expression is strongly repressed by miR-19a during the early phases of zebrafish development. In line with this observation and with a recent study showing that miR-19a is downregulated in a zebrafish Holt-Oram model, we now demonstrate that s1pr1 is upregulated in heartstring hearts. Next we investigated whether defects induced by s1pr1 upregulation might contribute to the morphological alterations caused by Tbx5 depletion. We show that downregulation of s1pr1 is able to partially rescue cardiac and fin defects induced by Tbx5 depletion. Taken together, these data support a role for s1pr1 in zebrafish cardiovascular development, suggest the involvement of this receptor in the Tbx5 regulatory circuitry, and further support the crucial role of microRNAs in early phase of zebrafish development.